Pemetaan penelitian komunikasi terapeutik di Indonesia melalui analisis Bibliometrik berbasis aplikasi VOSviewer - Lisnarini, Naurah; Rahman, Azizul; Gobel, Sry Ade Muhtya; Saputra, Dandi (Jurnal Informatio, 2025)
Therapeutic communication plays a crucial role in supporting the healing process and improving individual health, including mental health, education, and social interaction. It aims not only to exchange information but also to build empathetic relationships between healthcare providers and patients, creating a conducive environment for healing. This study maps research trends related to "therapeutic communication" in Indonesia over the past 5 years (2020-2024) through bibliometric analysis. Data was collected from Google Scholar using Publish or Perish (PoP) with specific keywords and analyzed and visualized using VOSviewer. The analysis reveals an increase in publication trends in 2023, likely due to the Covid-19 pandemic, which prompted extensive research on therapeutic communication. Increased interaction between patients and healthcare providers during the pandemic also influenced the quality of care. This study identifies five main focuses in therapeutic communication research: nursing, health, education, communication, and other fields. This study concludes that developing culturally sensitive therapeutic communication approaches and providing communication skills training for healthcare providers are crucial. This will create more inclusive and responsive healthcare services that meet community needs.